Space use by the giant anteater (Myrmecophaga tridactyla): a review and key directions for future research - Bertassoni, Alessandra; Ribeiro, Milton Cezar [UNESP] (Springer Nature, 2019)
Understanding the use of space is essential to promote effective conservation actions, particularly to xenarthran species that are threatened by habitat loss, poaching, and other environment degradation. Information regarding the use of space by the giant anteater (Myrmecophaga tridactyla), a large and vulnerable Neotropical mammal, is sparse and sometimes inconsistent in the scientific literature. Our aims are (1) to present an updated overview of giant anteater use of space; (2) to identify knowledge gaps; and (3) to recommend the next steps to advance this knowledge. We compiled information from 53 publications regarding the key aspects of space use: movement patterns, home range size and overlap, and habitat use. We identified the following research priorities: (a) the need of studies on different populations throughout the species’ range, including continuous native forest areas, and different spatial scales; (b) to develop research on dispersal by the individuals; (c) to understand movement patterns based on trajectory-related methods; (d) to comprehend home range overlap and territoriality ecological meaning; and (e) habitat selection and movement patterns on human-modified landscapes.
Keywords: Ecology; Home range; Movement; Neotropical vertebrate; Pilosa; Xenarthra